Factors affecting the financial structure of private insurance companies operating in Syria - اتيك, مايا; حنان ضاهر (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study aims to test the impact of factors affecting the financial structure of private insurance companies operating in Syria, which are 12 companies, using annual data, during the period (2009-2020). The independent variables are: tangible assets, liquidity, profitability, size, growth opportunities, risk, and taxes. The dependent variable, was measured by: (total debts/total assets), (total debts/equity). One of the Panel Data models was used which is a random effects model to test the relationship between the dependent variable and the independent variables. Inflation rate and GDP were included as control variables, in addition to the age of the company and Syrian crisis. The study showed that there is a significant negative effect for each of (tangible assets, profitability, liquidity, and economic growth rate) on the financial structure represented by (total debt to total assets), and there is a significant negative effect for each of (tangible assets, tax rate, profitability, liquidity), in the financial structure represented by (total debt to equity). A positive significant effect of the inflation rate in the financial structure represented by (total debts/equity), while there is no statistically significant effect of inflation in the financial structure represented by (total debts/total assets).